Use of ultrasound in pregnancy -opportunities and challenges for assessment of neurological development - Livrinova, Vesna (AD ZEGIN, 2024)
Advances in ultrasound technology and development of 4d have enabled evaluation of fetal movement and facial expressions in fetus.The purpouse of this test is to observe tne intrauterine neurological behavior of the fetus to predict developemnetal disorders.
In order to help and further develop knowledge for developmental disorders like Autism specter disorders and ADHD, experts from a lot of countries were invited. Elaboration of possible reasons, pathogenesis, treatment were presented.
Keywords: ultrasound; pregnancy; neurological; behavior; developmental; disorders